2020
DOI: 10.4025/actasciagron.v43i1.46862
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genetic variability on the quality of strawberry cultivars: sensorial, physical-chemical and nutritional characterization

Abstract: Strawberries are berry-type fruits that are very popular and widely consumed all over the world. The sensorial, physical-chemical and nutritional characteristics of strawberries are parameters of quality that influence the choices of consumers. However, these characteristics may be influenced by intrinsic and extrinsic factors that alter the fruit quality. The concentrations of nutrients and other chemical compounds in strawberries may increase and/or decrease according to the cropping system, maturation stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
2
5
0
1
Order By: Relevance
“…Content of compounds such as vitamin C are often regarded as one of the main health-related compounds present in strawberry fruits. It is mainly responsible for the antioxidant capacity of this fruit (Nunes et al 2021). Vitamin C was determined by HPLC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Content of compounds such as vitamin C are often regarded as one of the main health-related compounds present in strawberry fruits. It is mainly responsible for the antioxidant capacity of this fruit (Nunes et al 2021). Vitamin C was determined by HPLC.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that those fruits cultivated at high altitudes had higher contents of vitamin C than those at lower altitudes, independently of the variety. These differences were attributed to the genetic diversity and properties of the soil, as well as also to the conditions of growth (Nunes et al 2021). However, the correlation between this parameter and altitude must be further investigated, as was suggested by the inconsistent results reported by Doumett et al (2011) on wild strawberry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para la presente investigación la CSA que se seleccionó es la fresa (Fragaria x ananassa Duch) por las siguientes razones: 1) se considera un producto altamente perecedero (Cybulska et al, 2022); 2) es muy sensible a las prácticas de manipulación y a las condiciones de conservación durante poscosecha (Nunes et al, 2021;Zhang et al, 2020); 3) se encuentra priorizado por el Plan Estratégico de Ciencia, Tecnología e Innovación del Sector Agropecuario Colombiano -PECTIA; 4) existen demandas en Investigación, Desarrollo e Innovación en el departamento de Cundinamarca específicamente en el manejo y desarrollo de tecnología en poscosecha en la plataforma Siembra (http://www.siembra.gov.co/); y 5) se encuentra priorizado por el Plan Departamental de Extensión Agropecuaria -PDEA -2020-2024 de la Gobernación de Cundinamarca.…”
Section: Introductionunclassified
“…Moreover, it is considered a functional food since it contains bioactive compounds, including vitamin C, anthocyanins, and flavonoids, that have antioxidant activities (Afrin et al, 2016;Edger et al, 2019). Factors such as plant genetics, cultivation environment, fruit ripening, and post-harvest conditions affect the physical, biochemical, and sensory characteristics of strawberries (Hwang;Kim;Shin, 2019;Barth et al, 2020;Cervantes et al, 2020;Lalk et al, 2020;Nunes et al, 2021); therefore, these factors need to be considered when assessing the overall quality of the fruit.…”
Section: Introductionmentioning
confidence: 99%